Development of a production technology for cooked sausages using buckwheat extracts and their impact on quality and storage life - Akhundova, Nazilya; Babashli, Aynur (Eastern-European Journal of Enterprise Technologies, 2025)
The paper examines the production of meat sausages using buckwheat extracts, which possess antioxidant activity and are of great interest to the food industry. Adding buckwheat extract to cooked sausages has shown significant advantages in preserving quality and nutritional value. Products containing the extract retained their organoleptic properties longer and exhibited lower oxidation rates, confirming buckwheat's high antioxidant activity. The use of natural additives to enhance the quality and extend the shelf life of finished products is a relevant issue. The paper provides a detailed description of experimental results on different fat varieties, confirming the positive impact of buckwheat extracts on their oxidation stability. Research has revealed significant improvements in the moisture-binding capacity, as well as increased biological value of meat sausages. A recipe and production technology for cooked sausages using a meat additive containing buckwheat extract have been developed. The inclusion of this extract significantly slows down the accumulation of primary and secondary oxidation products and reduces the concentration of carbonyl compounds in the finished product. Adding buckwheat extract at 0.025 % by weight of fat to the sausage recipe proved particularly effective. The obtained results highlight the potential of buckwheat extracts as effective antioxidants that enhance the oxidation stability of meat sausages, improve their nutritional properties, and extend shelf life without synthetic preservatives. This provides a basis for implementation in real industrial production